Atendimento Educacional Especializado e Práticas Pedagógicas Inclusivas - Schmidt, Carlo; Menezes , Eliana da Costa Pereira de; Berni, Clenio Perlin; Vestena, Carla Luciane Blum; Schipper , Carla Maria de; Valentim , Bernadete de Fatima Bastos (Revista Educação Especial, 2021)
Editorial